Faktor yang Memengaruhi Niat Vaksinasi COVID-19 Pada Masyarakat Kabupaten Tangerang - Septiani, Putri Lia; Hamzens, Muhammad Farid (Journal of Religion and Public Health, 2022)
Background: COVID-19 is an infectious disease that is still a health problem that needs to be prevented by the whole community. One of the efforts to prevent COVID-19 is to carry out the COVID-19 vaccination. In the Theory of Planned Behavior (TPB), behavior of a person's COVID-19 vaccination can be predicted by the individual's intention. COVID-19 vaccination intention is also still a problem in the implementation of the COVID-19 vaccination program, especially in Tangerang Regency which in the preliminary study of this study showed 23/38 respondents (60.5%) did not intend to vaccinate against COVID-19. Methods: This type of research is quantitative with a cross sectional study design. The sample amounted to 200 people with a sampling technique using non-probability sampling with quota sampling type. The dependent variable of the study was the intention to vaccinate against COVID-19 and the independent variables were attitudes towards behavior, subjective norms, and perceptions of behavioral control, which were analyzed using the Chi-Square statistical test. Results: The results of this study showed that 74.5% of people aged 18 years in Tangerang Regency did not intend to be vaccinated against COVID-19. Most respondents have attitudes towards vaccination behavior with negative 50.5% COVID-19 vaccination intentions, negative subjective norms 77%, and negative behavioral control perceptions of 72%. All three have a significant relationship with the intention to vaccinate COVID-19.Keywords: Tangerang Regency, Intention of COVID-19 vaccination, Theory of Planned Behavior (TPB) AbstrakLatar Belakang: COVID-19 merupakan penyakit menular yang masih menjadi permasalahan kesehatan yang perlu dicegah oleh seluruh masyarakat. Salah satu upaya pencegahan COVID-19 adalah dengan melaksanakan vaksinasi COVID-19. Perilaku vaksinasi COVID-19 pada seseorang dapat diprediksi dengan niat individu yang dijelaskan dalam Theory of Planned Behavior (TPB). Niat vaksinasi COVID-19 ini juga masih menjadi permasalahan dalam pelaksanaan program vaksinasi COVID-19, khususnya di Kabupaten Tangerang yang pada studi pendahuluan penelitian ini menunjukkan 23/38 orang responden (60,5%) tidak berniat vaksinasi COVID-19. Metode: Jenis penelitian ini adalah kuantitatif dengan desain studi cross sectional. Sampel berjumlah 200 orang dengan teknik pengambilan sampel menggunakan non probability sampling dengan jenis quota sampling. Variabel dependen penelitian adalah niat vaksinasi COVID-19 dan variabel independennya sikap terhadap perilaku, norma subjektif, serta persepsi kontrol perilaku, yang dianalisis dengan uji statistic Chi-Square. Hasil: Hasil penelitian ini didapatkan 74,5% masyarakat usia ≥18 tahun di Kabupaten Tangerang tidak berniat divaksinasi COVID-19. Sebagian besar responden memiliki sikap terhadap perilaku vaksinasi dengan niat vaksinasi COVID-19 yang negatif 50,5%, norma subjektif negatif 77%, dan persepsi kontrol perilaku negatif 72%. Ketiganya memiliki hubungan yang signifikan dengan niat vaksinasi COVID-19.Kata Kunci: Kabupaten Tangerang, Niat vaksinasi COVID-19, Theory of Planned Behavior (TPB)